Role for Complement in the Development of Seizures following Acute Viral Infection - Libbey, Jane E. (American Society for Microbiology (ASM), 2010)
Complement, part of the innate immune system, acts to remove pathogens and unwanted host material. Complement is known to function in all tissues, including the central nervous system (CNS). In this study, we demonstrated the importance of the complement system within the CNS in the development of behavioral seizures following Theiler's murine encephalomyelitis virus (TMEV) infection. C57BL/6 mice, deficient in complement component C3, developed significantly fewer behavioral seizures following TMEV infection, whereas mice depleted of complement component C3 in the periphery through treatment with cobra venom factor had a seizure rate comparable to that of control mice. These studies indicate that C3 participates in the induction of acute seizures during viral encephalitis.